2022
DOI: 10.1111/dme.14911
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes self‐management during the COVID‐19 pandemic and its associations with COVID‐19 anxiety syndrome, depression and health anxiety

Abstract: Introduction The effects of the COVID‐19 pandemic on mental health have been profound. Mental health and diabetes self‐care are inter‐related. We examined whether COVID‐19 anxiety, depressive symptoms and health anxiety were associated with domains of diabetes self‐management and investigated whether greater COVID‐19 anxiety syndrome would independently contribute to suboptimal diabetes self‐care. Research design and methods Surveys were sent to people attending diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The C‐19ASS total score was positively and significantly associated with attentional bias ( r = 0.13, N = 286; Albery et al, 2021); burnout ( r = 0.42, N = 251; Asl, Boostani, et al, 2021); attachment style (RQ‐fearful attachment, r = 0.201; RQ‐preoccupied attachment, r = 0.14; RQ‐dismissing attachment, r = 0.022; N = 330; Vismara et al, 2022); loneliness ( r = 0.149, N = 330; Vismara et al, 2022); mental health problems ( r = 0.240, N = 330; Vismara et al, 2022); mask effectiveness , a component of mask‐wearing ( B = 0.08, SE = 0.23, p = 0.718, N of Study 1a = 147, Study 1b = 150; Krishna et al, 2021); communication difficulties , a component of mask‐wearing ( B = 0.20, SE = 0.17, p = 0.237, N of Study 1a = 147, Study 1b = 150; Krishna et al, 2021); clinic nonattendance (odds ratio [ OR ] = 1.106, 95% CI [1.047–1.17], p = 0.001); burnout ( r = 0.37, N = 251; Asl, Boostani, et al, 2021); psychological behavioural responses ( r = 0.767, N = 926; Sharif Nia et al, 2022); dietary control (glucose management, r = 0.01; N = 314; Distaso, Malik, et al, 2022); pandemic fatigue ( OR = 1.030, 95% CI [1.010–1.051], p = 0.003); and perceived COVID‐19 threat ( r = 0.48, N = 426; Nikčević & Spada, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The C‐19ASS total score was positively and significantly associated with attentional bias ( r = 0.13, N = 286; Albery et al, 2021); burnout ( r = 0.42, N = 251; Asl, Boostani, et al, 2021); attachment style (RQ‐fearful attachment, r = 0.201; RQ‐preoccupied attachment, r = 0.14; RQ‐dismissing attachment, r = 0.022; N = 330; Vismara et al, 2022); loneliness ( r = 0.149, N = 330; Vismara et al, 2022); mental health problems ( r = 0.240, N = 330; Vismara et al, 2022); mask effectiveness , a component of mask‐wearing ( B = 0.08, SE = 0.23, p = 0.718, N of Study 1a = 147, Study 1b = 150; Krishna et al, 2021); communication difficulties , a component of mask‐wearing ( B = 0.20, SE = 0.17, p = 0.237, N of Study 1a = 147, Study 1b = 150; Krishna et al, 2021); clinic nonattendance (odds ratio [ OR ] = 1.106, 95% CI [1.047–1.17], p = 0.001); burnout ( r = 0.37, N = 251; Asl, Boostani, et al, 2021); psychological behavioural responses ( r = 0.767, N = 926; Sharif Nia et al, 2022); dietary control (glucose management, r = 0.01; N = 314; Distaso, Malik, et al, 2022); pandemic fatigue ( OR = 1.030, 95% CI [1.010–1.051], p = 0.003); and perceived COVID‐19 threat ( r = 0.48, N = 426; Nikčević & Spada, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Also, the C‐19ASS total score was negatively associated with vigilance to threat (vigilance to threat, r = −0.03); slowed disengagement ( r = −0.12, N = 286; Albery et al, 2021); compassion ( r = −0.035, N = 251; Asl, Boostani, et al, 2021); attachment style (RQ‐secure attachment, r = −0.215, N = 330; Vismara et al, 2022); explicit evaluation of (masked) faces ( B = −0.45, SE = 1.97, p = 0.819; N of Study 1a = 147, Study 1b = 150; Krishna et al, 2021); mask‐related worrying , a component of mask‐wearing ( B = −0.04, SE = 0.23, p = 0.854, N of Study 1a = 147, Study 1b = 150; Krishna et al, 2021); aesthetic appeal , a component of mask‐wearing ( B = −0.06, SE = 0.18, p = 0.746, N of Study 1a = 147, Study 1b = 150; Krishna et al, 2021); resilience ( r = −0.110, N = 203; Oducado et al, 2021); organizational change ( b = −0.27, SE = 0.10, N = 112; Larasatie et al, 2022); perception of organizational politics ( B = −0.91, SE = 0.32, N = 112; Larasatie et al, 2022); and the Diabetes Self‐Management Questionnaire (DSMQ global, r = −0.06; physical activity, r = −0.10; physician contact, r = −0.13; N = 314; Distaso, Malik, et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the negative results of the pandemic involving mental health, other related factors were the fear of contagion by COVID-19 [82,83] and COVID-19 anxiety syndrome [84]. Studies reported that up to 27.3% of people with DM experienced stress due to the spread of the COVID-19 pandemic and 20% experienced stress due to fear of drug shortages [85].…”
Section: Discussionmentioning
confidence: 99%